2002
DOI: 10.1046/j.1468-1331.2002.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Vβ5.2/5.3 T cells with a humanized antibody in patients with multiple sclerosis

Abstract: A potentially pathogenic expansion of T cells expressing T cell receptor (TCR) Vbeta5.2/5.3 has been demonstrated in patients with multiple sclerosis (MS). A humanized antibody (ATM-027) directed against these T cells has been developed to further investigate the role of this subpopulation of T cells in MS. The pharmacokinetics/dynamics and safety of ATM-027 (0.3-300 mg intravenously over 30 min) were investigated in 14 patients with MS. The effect of treatment on cytokine expression and autoreactivity to pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…It is not necessarily unexpected to see a selected expansion of a particular V␤-restricted T-cell subset upon exposure to RSV G. Pathogenic roles for specific T-cell subsets in several models of infection and in various autoimmune diseases, including a disease-causing population of V␤14 ϩ CD8 ϩ T cells in a mouse model of ulcerative colitis (36), have been described (6,11,12,32,36,37). Several of those studies describe a protective effect of selected depletion of the particular T-cell subset associated with disease without any toxicity or observable effect in normal populations (6,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not necessarily unexpected to see a selected expansion of a particular V␤-restricted T-cell subset upon exposure to RSV G. Pathogenic roles for specific T-cell subsets in several models of infection and in various autoimmune diseases, including a disease-causing population of V␤14 ϩ CD8 ϩ T cells in a mouse model of ulcerative colitis (36), have been described (6,11,12,32,36,37). Several of those studies describe a protective effect of selected depletion of the particular T-cell subset associated with disease without any toxicity or observable effect in normal populations (6,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several of those studies describe a protective effect of selected depletion of the particular T-cell subset associated with disease without any toxicity or observable effect in normal populations (6,11). In fact, the deletion of the disease-causing T-cell subsets is an effective treatment for at least two autoimmune syndromes in humans (6,37). Thus, while studies have not described the effects of V␤14 ϩ -T-cell depletion in normal uninfected mice, these studies and the data reported here (for RSV-challenged mice primed with vac-lac or FI-RSV) would suggest that the elimination of this T-cell subset does not adversely affect the general immune status of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tomas Olsson and colleagues took these results forward into the clinic, targeting T cells with VB5.2 T-cell receptors. They substantially depleted T cells reactive to myelin basic protein that produced interferon (IFN)-γ (56).…”
Section: Early Years On the Stanford Facultymentioning
confidence: 99%
“…Currently it is being tested in patients with early active relapsing-remitting MS in a comparative study with IFN-β [2]. Alternatively, mAbs for treatment of MS are directed to the T cell receptor such as the T cell depleting humanized anti-Vβ5.2/5.3 T cell receptor-specific mAb ATM-027 [11]. On the other hand, a high affinity chimeric human-mouse anti-CD20 mAb that was originally generated to treat non-Hodgkin B cell lymphoma has recently been considered highly promising for the treatment of autoimmune diseases that are mainly Ab-mediated such as RA and SLE [1].…”
Section: ■ Therapymentioning
confidence: 99%